A Pragma - Dialectical study of speech ACT and argumentative Indicator in oxford union debate is Islam A Peaceful Religion ( 2013 ) - Kaulya Elfina Larasati (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2023)
et,1/Mumtaz c.1